Shifts in the Bacterial Community of Supragingival Plaque Associated With Metabolic-Associated Fatty Liver Disease - Zhao, Fen; Dong, Ting; Yuan, Ke-Yong; Wang, Ning-Jian; Xia, Fang-Zhen; Liu, Di; Wang, Zhi-Min; Ma, Rui; Lu, Ying-Li; Huang, Zheng-Wei (Frontiers in Cellular and Infection Microbiology, 2020)
Metabolic-associated fatty liver disease (MAFLD), also known as the hepatic manifestation of metabolic disorders, has become one of the most common chronic liver diseases worldwide. The associations between some oral resident microbes and MAFLD have been described. However, changes to the oral microbial community in patients with MAFLD remain unknown. In this study, variations to the supragingival microbiota of MAFLD patients were identified. The microbial genetic profile of supragingival plaque samples from 24 MAFLD patients and 22 healthy participants were analyzed by 16S rDNA sequencing and bioinformatics analysis. Clinical variables, including indicators of insulin resistance, obesity, blood lipids, and hepatocellular damage, were evaluated with laboratory tests and physical examinations. The results showed that the diversity of the supragingival microbiota in MAFLD patients was signiﬁcantly higher than that in healthy individuals. Weighted UniFrac principal coordinates analysis and partial least squares discriminant analysis showed that the samples from the MAFLD and control groups formed separate clusters (Adonis, P = 0.0120). There were 27 taxa with differential distributions (linear discriminant analysis, LDA＞2.0) between two groups, among which Actinomyces and Prevotella 2 spp. were over-represented in the MAFLD group with highest LDA score, while Neisseria and Bergeyella spp. were more abundant in the control group. Co-occurrence networks of the top 50 abundant genera in the two groups suggested that the inter-genera relationships were also altered in the supragingival plaque of MAFLD patients. In addition, as risk factors for the development of MAFLD, insulin resistance was positively correlated with the abundances of Granulicatella, Veillonella, Streptococcus, and Scardovia spp., while obesity was positively correlated to the abundances of Streptococcus, Oslenella, Scardovia, and Selenomonas spp. Metagenomic predictions based on Phylogenetic Investigation of Communities by Reconstruction of Unobserved States revealed that pathways related to sugar (mainly free sugar) metabolism were enriched in the supragingival plaque of the MAFLD group. In conclusion, as compared to healthy individuals, component and interactional dysbioses were observed in the supragingival microbiota of the MAFLD group.